Mapping outcomes for recovery of consciousness in studies from 1986 to 2020: a scoping review protocol. Issue 6 (30th June 2022) - Weaver, Jennifer; Cogan, Alison; Bhandari, Parie; Zainab, Bint-e Awan; Jacobs, Erica; Pape, Ariana; Nguyen, Chantal; Guernon, Ann; Harrod, Tom; ,; Bender Pape, Theresa; Mallinson, Trudy
Abstract : Introduction: Historically, heterogeneous outcome assessments have been used to measure recovery of consciousness in patients with disorders of consciousness (DoC) following traumatic brain injury (TBI), making it difficult to compare across studies. To date, however, there is no comprehensive review of clinical outcome assessments that are used in intervention studies of adults with DoC. The objective of this scoping review is to develop a comprehensive inventory of clinical outcome assessments for recovery of consciousness that have been used in clinical studies of adults with DoC following TBI. Methods and analysis: The methodological framework for this review is: (1) identify the research questions, (2) identify relevant studies, (3) select studies, (4) chart the data, (5) collate, summarise and report results and (6) consult stakeholders to drive knowledge translation. We will identify relevant studies by searching the following electronic bibliographic databases: PubMed, Scopus, EMBASE, PsycINFO and The Cochrane Library (including Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials and Cochrane Methodology Register). Criteria for article inclusion are published in the English-language, peer-reviewed studies of interventions aimed at facilitating recovery of consciousness among adults (> 18 years) with DoC following a severe TBI, published from January 1986 to December 2020. Articles meeting inclusion criteria at this stage will undergo a full text review. We will chart the data by applying the WHO International Classification of Functioning, Disability and Health Framework to identify the content areas of clinical outcome assessments. To support knowledge translation efforts, we will involve clinicians and researchers experienced in TBI care throughout the project from conceptualisation of the study through dissemination of results. Ethics and dissemination: No ethical approval is required for this study as it is not determined to be human subjects research. Results will be presented at national conferences and published in peer-reviewed journals. Trial registration number: CRD42017058383.